Формирование слоистой структуры в плёнках никеля при электроосаждении импульсным током - Штапенко, Э.Ф.; Заблудовский, В.А.; Титаренко, В.В.; Краева, В.С.; Афанасов, А.М. (Металлофизика и новейшие технологии, 2019)
The steel–molybdenum coating applied to the piston rings group made of high-strength cast iron provides a good conformability, low wear rate, and low coefficient of friction. This fact is explained by the specific characteristics of molybdenum oxides.